Electric vehicle range extension strategies based on improved AC system in cold climate – A review. (April 2018) - Zhang, Ziqi; Wang, Dandong; Zhang, Chengquan; Chen, Jiangping
Highlights: The state-of-art strategies of electric vehicle range extension are reviewed. Climate control load reduction methods are reviewed based on load characters. Different types of vehicle heat pump systems are introduced and compared. Abstract: The electric vehicles (EVs) are drawing much attention worldwide due to low fuel consumption and local pollution. However, the range of EVs is still not parallel to that of internal combustion engine vehicles. Moreover, the EV's range suffers a significant decrease in cold and hot climate due to the climate control load of the air conditioning system. These two combined making the range extension strategies a hot spot in EV research. In this paper, the review on EV range extension strategies is provided. First, the climate control load reduction strategies are reviewed. The characters of heating load in cold climate and the reduction methods are introduced. Second, the review on heat pump heating is conducted based on the different structures of heat pump systems. The combination of load reduction and heat pump heating seems to be a promising way in solving the range reduction problems.